Early stages of age-related macular degeneration: an immunofluorescence and electron microscopy study. - van der Schaft, T L (1993)
In subretinal neovascularisation capillaries originating from the choriocapillaris must cross Bruch's membrane to reach the subretinal pigment epithelial space. Thus gaps in Bruch's membrane have to be formed before subretinal neovascularisation. Histological examination of eyes with subretinal neovascularisation or disciform scars has shown macrophages adjacent to thin areas and ruptures in Bruch's membrane. This has been interpreted as phagocytosis of Bruch's membrane. The purpose of this study was to investigate whether immune complex depositions can be detected in maculae with early stages of age-related macular degeneration and to explain the macrophage reaction before the disciform reaction. A series of 20 human maculae were examined by direct immunofluorescence light microscopy to detect the presence of immune complexes with antibodies directed against immunoglobulins, fibrinogen, and complement factors. Transmission electron microscopy on several maculae was performed to identify the macrophages. Macrophages were observed in close relation to the readily recognisable long spacing collagen, which suggested that long spacing collagen was selectively internalised by these cells. Definite immune complex depositions were not found in basal laminar deposits or drusen. Linear deposits of fibrinogen and complement were frequently found in the outer collagenous zone of Bruch's membrane. However, because of the absence of immunoglobulins, it seems unlikely that these non-specific deposits might cause chemoattraction of macrophages and play a role in the initial phase of the development of subretinal neovascularisation and disciform macular degeneration.